(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the formation and preservation of Karakalpak national identity through the lens of contemporary visual art, grounded in ethnographic and documentary research conducted at the I.V. Savitsky State Art Museum in Nukus, Uzbekistan. Drawing on my dissertation, I analyze how Karakalpak identity—historically shaped by nomadism, oral tradition, and ecological hardships—has been visually articulated in the post-Soviet context. The works of artists such as Daribay Tureniyazov, Joldasbek Kuttimuratov, Alvina Shpadi, and Bazarbay Serekeev embody a collective memory shaped by folklore, myth, and lived experience. Using grounded theory and ethnographic fieldwork, this study reveals how art serves not only as a cultural archive but also as a means of resilience and national self-definition. By examining the intersection of artistic expression, ethnic heritage, and geopolitical transition, I argue for the essential role of art in sustaining Karakalpak identity amidst the forces of globalization, environmental degradation, and cultural marginalization.